Effects of aquatic exercise and progressive muscle relaxation on physical fitness, pain score and emotional distress among osteoarthritis patients - Kaarud, Eman Ahmed A. (2025)
Aquatic exercises and progressive muscle relaxation are commonly recommended as non-pharmacological treatments for individuals with osteoarthritis (OA); however, their effectiveness remains understudied. This study is designed to evaluate how aquatic exercise, progressive muscle relaxation, and their combination affect physical fitness, pain levels, and emotional distress (including depression, anxiety, and stress) in Malaysian knee osteoarthritis patients. It also focused on identifying practical intervention components. A total of 46 men and women with knee osteoarthritis diagnosed as grades II and III who met the inclusion criteria were randomly assigned to either an aquatic group (n = 11), a progressive muscle relaxation group (n = 11), a combination group (n = 12), or a control group (n = 12). Participants were recruited from the Orthopaedics clinic at Hospital Universiti Sains Malaysia (HUSM). All participants completed assessments for physical fitness (6-MWT, ROM), pain score (VAS, WOMAC pain), and emotional distress (DASS-21) at baseline, after 4 weeks (mid-intervention), after 8 weeks (post-intervention), and 12 weeks (end-intervention), respectively, at the Exercise and Sports Science Laboratory, Universiti Sains Malaysia (USM). The intervention consisted of a twelve-week programme, conducted twice weekly (totaling 24 sessions), which involved an aquatic exercise programme, progressive muscle relaxation training, and a combination of both over twelve consecutive weeks. Statistical analysis was performed using a mixed factorial ANOVA. Compared to the control group, all intervention groups experienced significant improvements in flexibility, walking distance, pain scores, anxiety, depression, and stress. The combined group showed additional improvements in physical fitness, as measured by the 6-MWT (485.75 ± 42.16 m, p = .00) and ROM (range of motion), flexion in the right knee (144 ± 6.88⁰, p = .00) and left knee (147 ± 3.98⁰, p = .00); extension in the right knee (0.00 ± 0.00⁰, p = .00) and left knee (0.00 ± 0.00⁰, p = .00)—often following the aquatic and PMR groups. Similarly, there were reductions in pain VAS score (13 ± 7.33 mm, p = .00), WOMAC-pain score (0.08 ± 0.28, p = .00), and emotional distress (depression 0.16 ± 0.30, p = .00; anxiety 0.00 ± 0.00, p = .00; stress 0.08 ± 0.28, p = .00). These improvements remained significant at weeks 8 and 12 of the intervention. Over 12 weeks, aquatic exercises, progressive muscle relaxation, and their combination, especially, led to significantly improved physical fitness, reduced pain, and alleviated emotional distress in patients with knee osteoarthritis compared to the control group. The combined approach consistently yielded the highest meaningful benefits across various outcome measures